Sequence-specific and polarized replication termination in vitro: complementation of extracts of tus- Escherichia coli by purified Ter protein and analysis of termination intermediates. - MacAllister, T (1990)
We have developed an in vitro replication system in which purified replication termination protein (Ter) elicits specific and polarized termination of DNA replication at terminator sites (tau) in a cell extract of tus- Escherichia coli that does not encode Ter protein. Using this system and two-dimensional agarose gel electrophoresis, we have identified intermediates with stalled replication forks. The replication bubbles contain both arrested leading strands and lagging strands that were initiated at the ColE1 origin of replication and that had progressed unidirectionally until arrested at tau. To dissect the system further, we have analyzed the kinetics of the formation of the termination intermediates and have discovered that the earliest termination intermediate had properties consistent with an arrested D loop. The D loop contained an arrested leading strand. Thus, in this test system, there appears to be a transient uncoupling of leading- and lagging-strand synthesis during termination of replication at tau sites.